Synthesis and characterization of graphite oxide and 2-methyl-4-chlorophenoxy acetic acidgraphite oxide (mcpa-go) nanocomposite with its controlled release property / Norilyani Izzati Hasanuddin - Hasanuddin, Norilyani Izzati (Faculty of Applied Sciences, 2017)
The graphite oxide and 2-methyl-4chlorophenoxy acetic acid- graphite oxide (MCPA-GO) nanocomposite were successfully synthesized by using improved Hummer's method and ion-exchange method respectively. In this study, MCPA-GO nanocomposite was synthesized at various concentration of MCP A ranging from 0.1 to 0. 7 M to lowering its toxicity and increase the drugs/herbicides loading efficiency. Meanwhile, the graphite oxide was prepared with the use the graphite powder as starting material. Graphite oxide and MCPA-GO nanocomposite were characterized using Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (PXRD) and Carbon Hydrogen Nitrogen and Sulphur analyzer (CHNS). The FTIR spectra of MCPA-GO nanocomposite was showed resemblance peaks of the MCPA and graphite oxide indicated the inclusion of MCP A into the graphite oxide. As for XRD pattern, there was increasing in the basal spacing of the nanocomposite from the graphite oxide which by 9.3 A to 9.7 A. Other than that, the percentage loading of MCP A in the nanocomposite was calculated to be 98.0 % (w/w) based on the CHNS result. Next, the controlled release ofMCPA-GO nanocomposite was done in two different solution which were in sodium chloride solution (NaCl) and sodium carbonate solution (Na2CO3). The release of MCP A into these solution was found to be dependent to the anion in the order of Na2CO3 > NaCl with the percentage release of 66 % and 10 % respectively. It proved that this release property exhibits the potential application of graphite oxide as effective nanocarrier of herbicides.